Literature Review: Efektivitas Penggunaan Media Edukasi Gizi terhadap Pengetahuan dan Sikap pada Siswa Sekolah Dasar Tentang Gizi Seimbang - Arneta Anggraeni Putri Sumantri; Ratih Kurniasari (UNIVERSITAS NGUDI WALUYO, 2022)
Elementary school students are students aged 6-12 years. Education can increase a person's knowledge, with an increase in knowledge it is expected that there will be changes in better behavior towards nutrition and health. A person will have good knowledge if that person can use his five senses to the maximum extent possible. To determine the effectiveness of nutrition education media on the knowledge and attitudes of elementary school students about Balanced Nutrition. The use of Android and the website is devastating for elementary school students in nutrition education so that it can have a positive impact on the use of smartphones and the internet. The use of puzzles as a medium for balanced nutrition education can generate high interest for students. The use of wayang media and booklets can easily identify and understand the role of each character in delivering nutrition education. The use of comics has various interesting animation images so that nutrition education delivered to elementary school students can be accepted more easily. The use of video on balanced nutritional behavior in students is because videos can be more easily accepted by students because they relate directly to their senses of sight and hearing. Several studies have shown that nutrition education media can change the behavior of elementary school students for the better. Each balanced nutrition education media is on average effective for use by elementary school student. ABSTRAK Siswa sekolah dasar merupakan siswa yang memiliki jenjang usia 6-12 tahun. Pendidikan dapat meningkatan pengetahuan seseorang, dengan adanya peningkatan pengetahuan diharapkan akan terjadi perubahan perilaku yang lebih baik terhadap gizi dan kesehatan. Seseorang akan memiliki pengetahuan yang baik apabila seoseorang tersebut dapat menggunakan panca indranya dengan semaksimal mungkin.Untuk mengetahui efektivitas media edukasi gizi terhadap pengetahuan dan sikap pada siswa Sekolah Dasar tentang Gizi Seimbang. Penggunaan Android dan website sengat efektif digunakan untuk siswa Sekolah Dasar dalam edukasi gizi sehingga dapat memberikan dampak positif dari penggunaan smartphone dan internet. Penggunaan puzzle sebagai media edukasi gizi seimbang dapat menimbulkan minat yang tinggi bagi siswa. Penggunaan media wayang dan booklet dapat dengan mudah untuk mengetahui dan memahami peran masing-masing tokoh dalam menyampaikan pendidikan tentang gizi. Penggunaan komik memiliki berbagai animasi gambar yang menarik sehingga edukasi gizi yang disampaikan kepada siswa Sekolah Dasar dapat diterima dengan lebih mudah. Penggunaan video terhadap perilaku gizi seimbang pada siswa karena video dapat lebih mudah diterima siswa karena mengaitkan langsung dengan indera penglihatan dan pendengarannya. Beberapa studi membuktikan bahwa media edukasi gizi mampu mengubah perilaku siswa Sekolah Dasar menjadi lebih baik. Setiap media edukasi gizi seimbang rata-rata efektif untuk digunakan oleh siswa Sekolah Dasar.